An Atrophic Plaque with Arborizing Vessels - Alejandra Villarreal-Martinez; Sonia Chavez-Alvarez; Maira Herz-Ruelas; Ivette Miranda-Maldonado; Osvaldo Vázquez-Martinez (Karger Publishers, 2016)
Dermatofibromas are a common finding in the daily clinical practice. Most lesions are found incidentally or because patients seek medical attention due to the aspect of the lesion. Rare variants of dermatofibroma such as aneurismatic or atrophic dermatofibroma can be encountered simultaneously; thus, these combined features may raise the possibility of other diagnoses to be considered. By providing diverse clinical and dermoscopic examples of dermatofibromas, we may prevent misdiagnosing these lesions. This case illustrates how two rare variants of dermatofibroma can coexist. Clinical presentation of dermatofibromas may vary greatly, and it is essential for dermatologists to recognize them clinically and dermoscopically before obtaining histopathological diagnosis.